2009
DOI: 10.1021/bi900057g
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Mutant Tyrosine Kinase Chemical Rescue

Abstract: Protein tyrosine kinases are critical cell signaling enzymes. These enzymes have a highly conserved Arg residue in their catalytic loop which is present two residues or four residues downstream from an absolutely conserved Asp catalytic base. Prior studies on protein tyrosine kinases Csk and Src revealed the potential for chemical rescue of catalytically-deficient mutant kinases (Arg to Ala mutations) by small diamino compounds, particularly imidazole, however the potency and efficiency of rescue was greater f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 38 publications
2
27
0
Order By: Relevance
“…However, the chemical rescue of the R390A c-Src mutant provides a strategy that perfectly fits this purpose because it provides a rapid, specific, and reversible mechanism of c-Src activation by the small molecule imidazole, allowing the detection of the immediate effects of the restored c-Src activity in cells (3). Prior in vitro studies on the tyrosine kinases Csk, Src, and Abl have indicated that the imidazole concentration used here (Ͻ30 mM) has no effect (Ͻ10%) on wild-type kinase activity (3,12,14). Furthermore, previous experiments on chemical rescue of R/A Csk and Src with imidazole in cell culture have revealed that this chemical rescue approach recapitulates, without apparent toxic effects, expected tyrosine kinase activities involved in stress fiber formation, vascular tube formation, cell migration and transformation, and guanylyl cyclase modulation (3, 12-14, 53, 54).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the chemical rescue of the R390A c-Src mutant provides a strategy that perfectly fits this purpose because it provides a rapid, specific, and reversible mechanism of c-Src activation by the small molecule imidazole, allowing the detection of the immediate effects of the restored c-Src activity in cells (3). Prior in vitro studies on the tyrosine kinases Csk, Src, and Abl have indicated that the imidazole concentration used here (Ͻ30 mM) has no effect (Ͻ10%) on wild-type kinase activity (3,12,14). Furthermore, previous experiments on chemical rescue of R/A Csk and Src with imidazole in cell culture have revealed that this chemical rescue approach recapitulates, without apparent toxic effects, expected tyrosine kinase activities involved in stress fiber formation, vascular tube formation, cell migration and transformation, and guanylyl cyclase modulation (3, 12-14, 53, 54).…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that mutation of a highly conserved Arg (390 in c-Src) in protein-tyrosine kinases re-sults in a dramatic reduction in catalytic activity (200 -5000-fold), presumably because of the loss of a key hydrogenbonding side chain responsible for orienting the substrate tyrosine phenol for phosphoryl transfer (12)(13)(14). A variety of di-and triamino compounds added to the enzyme reaction buffer have been shown to complement this defective kinase activity, the most efficient being imidazole (12)(13)(14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The insoluble pellet was resuspended in 8 M urea, diluted 1:10 in suspension buffer, incubated with glutathione agarose (Sigma) and washed three times before use as substrate for in vitro phosphorylation (described below). Purified recombinant wildtype Abl kinase domain (residues 229-511) (Seeliger et al, 2005) and corresponding mutant R367A (Muratore et al, 2009) were gifts from Philip Cole (Johns Hopkins School of Medicine, Baltimore, MD).…”
Section: Recombinant Proteinsmentioning
confidence: 99%
“…We tested emerin as a potential substrate for the purified recombinant His-tagged kinase domain (residues 229-511) of human Abl (Seeliger et al, 2005). As the control, we used Abl mutant R367A, which has 5000 times lower catalytic efficiency (Muratore et al, 2009). Recombinant His-tagged emerin (residues 1-176) was incubated 30 minutes alone or with each Abl kinase domain.…”
mentioning
confidence: 99%